Bioekologi Udang Swallow (Penaeus merguiensis) - Sri Murni; Rivo Hasper Dimenta (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to examine the bioecological aspects of P. merguiensis around the estuary of the Berombang river in terms of growth patterns, the abundance of gonad maturity and condition factors. The method used in this research is purposive sampling. Shrimp sampling was carried out using arad nets which were stocked at low tide. The results showed that the composition of the abundance of the gonadal maturity level of P. merguiensis shrimp at three sampling stations was dominated by immature gonadal shrimp (BMG) to TKG 2. The growth pattern of P. merguiensis shrimp based on the length-body weight relationship in the Berombang river was classified as positive allometric. Fulton condition factor (K) ranged from 0.14 to 4.68, with an average total body length ranging from 2.35 to 13.70 cm. In conclusion, the condition factor of P. merguiensis shrimp in the Berombang river was classified as a plump category with shrimp weight gain being faster than body length growth, with female plumpness being greater than males. Keywords: Fulton Condition Factor, Gonad Maturity, Growth Pattern, P. merguiensis, Berombang River